2010
DOI: 10.1007/s11306-010-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite profiling approach to follow the sprouting process of mung beans (Vigna radiata)

Abstract: A metabolite profiling methodology based on capillary gas chromatography/mass spectrometry (GC/MS) was employed to investigate time-dependent metabolic changes in the course of the sprouting of mung beans (Vigna radiata). Intact mung beans and sprout samples taken during the germination process were subjected to an extraction and fractionation procedure covering a broad spectrum of lipophilic (e.g. fatty acid methyl esters, hydrocarbons, fatty alcohols, sterols) and hydrophilic (e.g. sugars, acids, amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…Quantities of acids significantly increased over the germination process of black gram. A considerable increase in amino acid levels has also been reported in sprouting mung bean (Na Jom et al 2011) and pea (Kuo et al 2004). It should be noted that changes of amine, amino acid, organic acid and inorganic acid contents in black gram over the germination process are highly influenced by the respective sprouting temperature.…”
Section: Impact Of Sprouting Temperaturementioning
confidence: 91%
See 3 more Smart Citations
“…Quantities of acids significantly increased over the germination process of black gram. A considerable increase in amino acid levels has also been reported in sprouting mung bean (Na Jom et al 2011) and pea (Kuo et al 2004). It should be noted that changes of amine, amino acid, organic acid and inorganic acid contents in black gram over the germination process are highly influenced by the respective sprouting temperature.…”
Section: Impact Of Sprouting Temperaturementioning
confidence: 91%
“…The powder was extracted and fractionated into four parts according to an established method (Na Jom et al 2011). The metabolite profiling allowed the detection of a broad range of nonpolar (e.g., fatty acid methyl esters, hydrocarbons, fatty alcohols and sterols) and polar (e.g., sugars, sugar alcohols, acids, amino acids and amines) low molecular weight compounds.…”
Section: Sample Extraction Fractionation and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Initial applications of metabolic profiling were largely focused on the model plant Arabidopsis thaliana (von Roepenack-Lahaye et al, 2004; Tohge et al, 2005; Gibon et al, 2006; Trenkamp et al, 2009; Araujo et al, 2010; Kerwin et al, 2011), however, several studies have been carried out on the green algae Chlamydomonas reinhardtii (Giroud et al, 1988; Bolling and Fiehn, 2005; May et al, 2008; Boyle and Morgan, 2009; Renberg et al, 2010) with other successful applications being reported for Catharanthus roseus (Rischer et al, 2006), Fragaria x ananassa (Aharoni et al, 2000, 2002; Hanhineva et al, 2008), Hordeum vulgare (Widodo Patterson et al, 2009), Medicago truncatula (Achnine et al, 2005), Nicotiana tabacum (Goossens et al, 2003), Oryza sativa (Albinsky et al, 2010), Perilla frutescens (Yamazaki et al, 2008), Pisum sativum (Jom et al, 2010), and Solanum lycopersicum (Schauer et al, 2005, 2006; Moco et al, 2006; Fraser et al, 2007) as well as the unicellular prokaryotes Synechocystis sp. (Krall et al, 2009) and the diatom Phaeodactylum tricornutum (Allen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%